2017
DOI: 10.1159/000476001
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Osteopontin Predicts Incident Chronic Kidney Disease, while Plasma Osteopontin Predicts Cardiovascular Death in Elderly Men

Abstract: Background and Objectives: The matricellular protein osteopontin is involved in the pathogenesis of both kidney and cardiovascular disease. However, whether circulating and urinary osteopontin levels are associated with the risk of these diseases is less studied. Design, Setting, Participants, and Measurements: A community-based cohort of elderly men (Uppsala Longitudinal Study of Adult Men [ULSAM]; n = 741; mean age: 77 years) was used to study the associations between plasma and urinary osteopontin, incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 26 publications
1
7
1
Order By: Relevance
“…With renal damage, osteopontin expression is significantly upregulated in all tubule segments and the glomeruli [41]. We confirm that high urinary osteopontin levels are predictors of renal structural damage and proteinuria without [42] and with LN [43]. Notably, osteo- pontin levels were often lower in patients with substantial damage as compared to that in no/minimal LN damage, even after adjustment for concurrent LN activity (NIH-AI).…”
Section: Discussionsupporting
confidence: 59%
“…With renal damage, osteopontin expression is significantly upregulated in all tubule segments and the glomeruli [41]. We confirm that high urinary osteopontin levels are predictors of renal structural damage and proteinuria without [42] and with LN [43]. Notably, osteo- pontin levels were often lower in patients with substantial damage as compared to that in no/minimal LN damage, even after adjustment for concurrent LN activity (NIH-AI).…”
Section: Discussionsupporting
confidence: 59%
“…Studies using rat models of accelerated antiglomerular basement membrane glomerulonephritis (Lan et al, 1998), subtotal (5/6) renal mass ablation (Yu et al, 2000), and streptozotocin-induced diabetes (Fischer et al, 1998) have similarly concluded that with injury renal osteopontin expression is upregulated. The upregulated osteopontin in said models is correlated with proteinuria, and macrophage and monocyte accumulation within the kidney (Fischer et al, 1998;Lan et al, 1998;Yu et al, 2000) making its urinary excretion a biomarker of kidney injury (Phillips et al, 2016;Feldreich et al, 2017). Urinary osteopontin concentrations were increased by HSD-feeding, and among the HSD-fed groups were lowest in SAC/C21 treated OZR.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously found several of these proteins to be inflammatory chemokines, cytokines, and growth factors, which are associated with atherosclerosis and incident CVD [ 19 , 20 , 21 ]. We have also found plasma osteopontin to be associated with incident CVD [ 12 ]. Given the tight coupling between osteopontin and several inflammatory chemokines, cytokines, and growth factors demonstrated both by traditional statistics as well as protein–protein interaction network analysis, it is hard to separate the role of osteopontin in CVD from the other proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma and urine osteopontin were measured using a commercial sandwich enzyme-linked immunosorbent assay (ELISA) kit (DY1433, R&D Systems, Minneapolis, MN, USA), as previously reported [ 12 ]. The limit of quantification (LOQ) of the Osteopontin ELISA was 62 pg/mL.…”
Section: Methodsmentioning
confidence: 99%